A STEP/EXPRESS to object–oriented database translator. (4th August 2014) - Goh, A.; Hui, S.C.; Song, B.; Wang, F.Y.
It may be expected that the natural choice of database model for storing the STEP model would be object–oriented, rather than relational or physical files. The paper examines this assumption from the view point of accuracy of representation, ease of access and performance. It further focuses attention on a translator which is able to convert a standard part required by product models from it STEP definition to object–oriented database constructs.